Diversity of Butterflies on Gunung Serambu, Sarawak, Malaysia - Sing Tyan, Pang; Alexander Kiew, Sayok; Mathew, Jenang (Springer International Publishing, 2016)
Gunung Serambu, a mountain in western Sarawak, northern Borneo, was occupied by the Bidayuh ethnic group, and abandoned about a century ago, with their settlement at the foothill of the mountain. The present study attempts to document butterflies, as part of a multidisciplinary study on this mountain, with the aim of conservation and sustainable use of the site. Three surveys of 4 days each were conducted from September 2012 to March 2013, using aerial nets and baited traps, that recorded 377 butterflies from 97 species. About 81 % (303 butterflies) of the captures were from the Nymphalidae, comprising 61 species, followed by the Lycaenidae with 24 individuals from 16 species. Baited traps captured less butterflies (163 compared to 214 by aerial traps), all from the Nymphalidae indicating that the method may have limitations in such studies. With the addition of 58 species that were considered new records, Gunung Serambu has 111 recorded species. Species accumulation curve suggest more additional records with time. Furthermore, with 46 species (more than 47 %) singletons and 21 species (22 %) doubletons, as well as the increasing species accumulation curve, longer sampling is warranted, covering different times of the year, as well as additional sites.